Analysis of Difficulties Japanese Language Education Program Student in Improving Student Motivation at Teaching Practice - Pratidina, Luthfia; Diner, Lispridona; Oesman, Andy Moorad (Chi'e: Journal of Japanese Learning and Teaching, 2018)
The purpose of this research is to find out the difficulty, causal factors and solutions when Japanese language education students having difficulty in motivating students at teaching practice(PPL). Approach in this research is descriptive quantitative and qualitative. Sample in this research is student of Prodi Pendidikan Bahasa Jepang class of year of 2013 which have executed PPL as many as 52 people. Data collection techniques used in this study is by questionnaire method. The questionnaire used in the form of semi-open questionnaire where the answer has been provided but also accompanied by a free reason filled by the respondent. Based on the result of research, it can be concluded that the difficulties experienced by the students are difficulties in understanding the factors that influence the motivation of learning (62.8%) and the difficulties in understanding the strategies in improving students' learning motivation (72.5%). The cause of the difficulty is because the students do not read the reference about motivation to learn. In addition 57.7% of the environmental conditions are also less supportive to make students motivated in learning. Solutions that students often do when having difficulties are discussing with the teacher (86.5%) and discussing with PPL friends (88.5%). Tujuan dari penelitian ini adalah untuk mengetahui kesulitan yang dialami mahasiswa Prodi Pendidikan Bahasa Jepang angkatan tahun 2013 dalam meningkatkan motivasi belajar siswa saat PPL, faktor penyebab kesulitan dan solusi yang dilakukan mahasiswa ketika mengalami kesulitan tersebut. Pendekatan dalam penelitian ini adalah deskriptif kuantitatif dan kualitatif. Sampel dalam penelitian ini adalah mahasiswa Prodi Pendidikan Bahasa Jepang angkatan tahun 2013 yang telah melaksanakan PPL sebanyak 52 orang. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah dengan metode angket. Angket yang digunakan berupa angket semi terbuka dimana jawaban sudah disediakan namun juga disertai alasan yang bebas diisi oleh responden. Berdasarkan hasil penelitian, dapat disimpulkan bahwa kesulitan yang dialami mahasiswa adalah kesulitan dalam memahami faktor-faktor yang mempengaruhi motivasi belajar (62,8%) dan kesulitan memahami strategi dalam meningkatkan motivasi belajar siswa (72,5%). Penyebab kesulitan tersebut dikarenakan mahasiswa kurang membaca referensi tentang motivasi belajar. Selain itu 57,7% kondisi lingkungan juga kurang mendukung untuk membuat siswa termotivasi dalam belajar. Solusi yang sering dilakukan mahasiswa ketika mengalami kesulitan adalah berdiskusi dengan guru pamong (86,5%) dan berdiskusi dengan teman PPL (88,5%).